Educational Access Inequalities in Rural Balochistan: A Gender Perspective - Ali, Sajid; Uzair-ul-Hassan, Muhmmad; Uzair, Iram (ACADEMIA International Journal for Social Sciences, 2025)
The situation in Rural Balochistan demonstrates certain inequalities in the access to primary and elementary school education where girls encounter intertwined socio-cultural, economic, geographic, and safety limitations. The paper looks at the gendered impediments to enrolment, attendance, and retention of Grades (1-8) in rural Balochistan, via the lens of parents. The qualitative case-study design was applied. Thirty-five (35) purposively chosen parents (mothers and fathers) were interviewed using semi-structured and face to face interviews. The interviews were recorded in audio in (Balochi/Urdu), transcribed and translated to English and analyzed through thematic analysis. The study is theoretically informed by Social Reproduction Theory, Feminist Theory, and the Capability Approach, which together explain how structural inequality, patriarchal norms, and restricted life opportunities shape girls’ educational exclusion. Findings explored Poor school facilities and teacher absenteeism, direct and indirect school expenses and the cost of domestic labor of girls including distance, lack of transport and fear of harassment; oppressive norms which refers to the cultural practice of female seclusion, often associated with maintaining modesty and protecting family honor and tradition of Balochistan; early marriage expectations; and a scarcity of female teachers, all led to a lack of trust in schools as girls’ safe places. The exclusion of girls is one of the indicators of limited real possibilities, but not absence of desire. To enhance retention in rural areas, gender responsive, and integrated interventions are required.